Drones and Support for the Use of Force - Walsh, James Igoe (University of Michigan Press, 2018)
Drones and Support for the Use of Force utilizes experimental research to analyze the effects of combat drones on Americans' support for the use of force. The authors develop expectations drawn from social science theory and then assess these conjectures using a series of survey experiments. Their findings-that drones have had important but nuanced effects on support for the use of force-have implications for democratic control of military action and civil-military relations, and provide insight into how the development and proliferation of current and future military technologies influence the domestic politics of foreign policy.